Assessment Of The Impact Community-Driven Development Project On Rural Farming Communities. A Case Of Fadama Ii In Adamawa State, Nigeria - Madu Umar, Adamu (Universiti Malaysia Sarawak (UNIMAS), 2013)
Fadama II project which is the largest agricultural and rural development project in Nigeria was designed to reduce poverty by providing support to the communities to acquire infrastructure and productive assets, providing demand-driven advisory services and enhancing the capacity of communities to manage economic activities, and reducing conflicts among resource users (Nkonya & Davis, 2008). These laudable objectives were to be achieved by adopting people centered development approach as set against the mandate of the project. It is important to note here that this CDD project is first of its kind in the study area. The focus of this study therefore is to assess the effect of this CDD project on the benefiting rural farming communities in Adamawa State, Nigeria